Sharia People's Trade Market as a Solution to Transform the Halal Business Axis of the Community in Indonesia - Hidayat, Muhammad Rizal; Prakoso, Lindhu Dwi; Nugroho, Aditya Febriansyah; Wongsokarto, Misdiarso; Santosa, Purbayu Budi (Al-Sharf: Jurnal Ekonomi Islam, 2025)
This research aims to design and propose a futuristic Islamic Economic idea in Indonesia namely sharia society market. This research was complied using descriptive qualitative method with causal comparative and development manner. This research result demonstrates the design model of sharia society market in terms of concept and application. This idea organizes several dimensional approaches such as sharia, fiqh, economic, and anthropology. The Sharia Society Market has prepared as a revolution in the halal real sector business axis of society in Indonesia.